+0  
 
0
190
1
avatar

3h-4k=5 5h+3k=-11

how to solve with elimination

Guest Feb 20, 2017
 #1
avatar
+5

Solve the following system:
{3 h - 4 k = 5 | (equation 1)
5 h + 3 k = -11 | (equation 2)
Swap equation 1 with equation 2:
{5 h + 3 k = -11 | (equation 1)
3 h - 4 k = 5 | (equation 2)
Subtract 3/5 × (equation 1) from equation 2:
{5 h + 3 k = -11 | (equation 1)
0 h - (29 k)/5 = 58/5 | (equation 2)
Multiply equation 2 by 5/29:
{5 h + 3 k = -11 | (equation 1)
0 h - k = 2 | (equation 2)
Multiply equation 2 by -1:
{5 h + 3 k = -11 | (equation 1)
0 h+k = -2 | (equation 2)
Subtract 3 × (equation 2) from equation 1:
{5 h+0 k = -5 | (equation 1)
0 h+k = -2 | (equation 2)
Divide equation 1 by 5:
{h+0 k = -1 | (equation 1)
0 h+k = -2 | (equation 2)
Collect results:
Answer: |h = -1           and          k = -2

Guest Feb 20, 2017

11 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.